Intimate partner violence among women living with human immunodeficiency virus attending a tertiary health facility in southwest Nigeria. (2023)
Globally intimate partner violence (IPV) is a major health problem and disproportionately affects more women than men. In Africa, women living with human immunodeficiency virus (HIV) face increased IPV risk, low record of disclosure and higher chance of transmission of HIV to their spouse. This study determined the prevalence and pattern of IPV and its association with disclosure status to partner among women living with HIV(WLHIV). This was a mixed method study among WLHIV attending HIV Anti-Retroviral (ART) clinic at the University College Hospital, Ibadan. Data was collected from 316 participants selected by systematic random sampling using a semi-structured questionnaire developed by the researcher. In-depth interviews were conducted among 20 participants using a guide. Frequency, percentages and proportion were used to summarize categorical variables and means and standard deviation for continuous variables. The test of association was by Chi square and statistical significance was set at p<0.05. Mean age of participants was 37.6 (7.4) years and most, 146(46.2%) were aged 30-39 years. One hundred and sixty-eight (53.2%) of the participants had IPV. The most reported form of IPV was physical 92(54.7%) while emotional and sexual accounted for 59 (35.1%) and 17 (10.2%) respectively. Two hundred and seventeen (69.0%) had disclosed their status to their partner and 69(21.9%) of their partners were HIV positive. The participants' perspectives about IPV were appropriate. There was a statistically significant association between non-disclosure of HIV status and increased prevalence of IPV (p<0.005). The study observed that there is high prevalence of IPV among WLHIV, especially where there is non-disclosure of HIV status to partner. There is need to encourage disclosure of HIV status to partners and more public enlightenment to reduce IPV.